International trade and political conflict : commerce, coalitions, and mobility - Hiscox, Michael J., 1966- (Princeton University Press, 2002)
Using evidence from political history, case studies and quantitive analysis, this guide debates whether class conflict or group competition is more prevalent in politics. It discusses the forces shaping trade policy outcomes.